PERANCANGAN SISTEM INFORMASI BERBASIS WEB PADA GOPALA TOUR AND TRAVEL - Gde Krishna Sankya Yogeswara; I Ketut Gede Suhartana; I Made Widiartha (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
A tour and travel website was developed to improve the efficiency of online information delivery and service booking for Gopala Bali Tours. The system enables customers to view tour packages, transportation services, and make direct reservations through a responsive online form accessible across devices. This replaces previous manual methods of promotion and booking via social media or direct communication, thereby streamlining service processes and enhancing the company’s professional image. An admin dashboard is also provided to allow business owners to independently manage content and monitor booking data. Socialization and training sessions were conducted to ensure effective system use. Evaluation results indicate that the website is user-friendly, informative, and contributes positively to the digital transformation of tourism services.